STUDY OF CHEDANA KARMA IN SURGICAL PRACTICE - Jibi T, *Varghese; Shah, Chitanya; Wagh, Rupesh; Shiralkar, Mayur; Tamhane, Vishal (AYUSHDHARA, 2016)
Chedana Karma is the foremost surgical procedure. It is needed to study and update the principles of Chedana Karma. Chedana is the foremost procedure adopted in surgical practice. All the Brihat-trayees have given prime importance to Chedana Karma and have explained it in various contexts. The term Chedana in Ayurvedic classical texts and the term ‘excision’ used in modern surgical textbooks are having same meaning. While exploring the surgical disorders explained under the indications of Chedana Karma and excision, many of the days are missing under the list of indications. However Sushruta while enumerating the name of the diseases and their management has given scope to the surgeons to add as well as to redesignate the disorders by using their knowledge. Objective is to study the concept of Chedana Karma in detail and evaluate its role in surgical practice. 10 different surgical excisional procedures are observed regarding their clinical features and compared with the conditions explained by Sushruta. The conditions told by Sushruta are found in varying numbers but not a single disease without them. Chedana and excision are synonymous. Features mentioned by Sushruta bear importance as they cover all the surgical diseases indicated for excision. Conditions of Apaka, Kathinya, Sthirata and Kotha explain all the possible indications for excision in any disease. The principles of Chedana Karma are studied thoroughly and comparison is done with the principles of excision by reviewing the literatures in Ayurveda as well as modern textbooks of surgery.